Multiple teams, multiple projects, multiple groups at the intersection of (multiple) research fields: A bibliometric study - Meslec, Nicoleta; Curseu, Petru Lucian; Fodor, Oana C.; Batistič, Saša; Kenda, Renata (Frontiers in Psychology, 2023)
Multi-teaming is a concept studied across a variety of disciplines. While using a bibliometric approach on 255 research papers extracted from Web of Science, we aimed to depict the architecture of the multi-teaming concept across academic disciplines and time. Results of citation, co-citation and bibliographic coupling analyses identified four major fields looking at the concept of multi-teaming. The fields emerged over time from fragmentation to integration and acknowledging similarities. We identify gaps and propose (multi)-disciplinary research ideas that can benefit the field of multi-teaming.